Google class in ELT: A study of Student's Responses in English for Nutrition - Saputri, Tiyas; Afandi, Mujad Didien; Alamsyah, Badril (IJET (Indonesian Journal of English Teaching), 2020)
Google classroom (GC) is one of the best platforms produced by Google that has some purposes for education, especially in teaching and learning process. In S1 Nutrition department, the application of Google Classroom is still rarely used and still few lecturers of Nahdlatul Ulama University of Surabaya use this application maximally for teaching any courses, including in teaching English. This research aims to find out the students’ responses of using GC in English Class of nutrition profession. This paper also presents GC features and the benefits of using it. The participants have had some experiences in using it. The participants are 37 students from three classes chosen through random sampling. The data was collected through questionnaire survey from the students’ responses. The data then was analyzed qualitatively. The results presented that from statement 1-10, only statement 1 (GC can accommodate e-learning) and statement 9 (GC is easy to use) which have reached 64,9% (Agree). The lowest percentage was 45,9% (GC is as a character building). They agreed that GC has many benefits and the priorities of benefit to accommodate e-learning and easy to use. However, it still needs to be explored further of the directly impact to the students for building their character.